The roles of xanthan gum, potato starch, and sorbitol in the formulation of gluten free bread - Azwin, Ahmad (2019)
Breads is a staple food for everyday life and the most difficult product to replace for celiac. Celiac disease is a lifelong inflammatory disease in small intestine caused by exposure to gluten. Gluten is a composite of storage proteins term prolamins and glutelins, where it is major component in bakery product. Cutting off the gluten will disrupt the technological structure of the dough. The effects of various experimental parameters in optimizing the bread formulation were studied using a Box-Behnken design methodology. A three level with three responses, which combined with response surface modelling, it was used to optimise the formulation. The results showed, 1.04g of xanthan gum, 40g potato starch and 5.15g sorbitol required for optimized formulation with rice and tapioca flour as a main ingredient. At this optimum condition, the firmness of bread crumb was reduced by 2.63N, but the weight and volume were maximized by 401.65g and 891.78cm3. Respondents give a score of 8.30 while the trained panel give a score of 8.44, representing the atribute of like very much in the optimum formulation. Nine trained panels give score of 7.78 for taste, 1.00 for crumb firmness and 8.44 for aroma. The colour of bread crust was L=70.35, a=5.80, and b=25.59, which has pale crust colour. The colour of bread crumb was L=80.51, a=-1.65 and b=10.84, show it has white crumb color approaching the color of white bread in the market. The nutritional contents showed the optimized bread have 81.14% carbohydrate, 8.85% crude protein, 7.86% crude fat, 0.69% of fibre and 2.15% of ash content. The shelf life of bread is 5 days, by observing moulds growth on the first day. The staling rate increased 5.6N and the moisture content decreased 1.2% after 72 hours of baking. Consequently, the staling rate can be slowed down by increasing the moisture content in the bread crumb. The microbial analysis in total plate count during 24 hours incubated is 1.5x101 then grown up to 5.3x104 after 72 hours. The moulds count during 24 hours was 1.3x101 and grown up to 6. 5x104 after 72 hours. As a conclusion, the response surface methodology had aided in optimizing a gluten free bread formulation. The addition of xanthan gum, potato starch and sorbitol with the exact amount has improved the quality of bread produced by reducing crumb firmness, increase volume expansion and weight of loaf. Furthermore, the bread has a good sensory acceptance’s, and sugar free without chemical additive or preservative.